1998
DOI: 10.2500/108854198778612654
|View full text |Cite
|
Sign up to set email alerts
|

β-Hexosaminidases: Potent Mitogens of Airway Smooth Muscle

Abstract: beta-Hexosaminidases A & B, inflammatory marker enzymes, are mannosyl-rich glycoproteins that are implicated in acute asthma. At physiologically and pathologically relevant concentrations (nM), beta-Hexosaminidases act as potent mitogens of bovine airway smooth muscle cells. This mitogenic action is mediated via 175 kD mannose recognizing receptors that have been isolated from bovine airway smooth muscle cells and human bronchial smooth muscle. There seems to be an involvement of multiple signal transduction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The pattern of β-hex-induced p44/42 MAPK is probably critical to cell proliferation [28,29,30]. Moreover, β-hex is protease resistant [26] and, upon activation, first degrades the extracellular matrix and subsequently acts as a mitogenic factor [27]. Thus, β-hex may serve as a key inflammatory mediator critical to the airway remodeling process [26] and the mitogenic activity of this enzyme in humans is very likely; however, more studies are needed to establish its precise role in airway remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern of β-hex-induced p44/42 MAPK is probably critical to cell proliferation [28,29,30]. Moreover, β-hex is protease resistant [26] and, upon activation, first degrades the extracellular matrix and subsequently acts as a mitogenic factor [27]. Thus, β-hex may serve as a key inflammatory mediator critical to the airway remodeling process [26] and the mitogenic activity of this enzyme in humans is very likely; however, more studies are needed to establish its precise role in airway remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that this enzyme could participate in airway inflammation and remodeling. β-hex and other mannosyl-rich lysosomal hydrolases are potent mitogens for bovine airway smooth muscle cells [24], and this mitogenic action is mediated via airway smooth muscle mannose-recognizing receptors [25] that have been isolated from bovine airway smooth muscle cells and human bronchial smooth muscle [26]. Lew et al [27] demonstrated that β-hex-induced airway smooth muscle cell proliferation is mediated by activation of p21Ras/MEK/p44/42 MAPK and protein kinase C. β-hex causes activation of p44/42 MAPK that is late in onset (30 min) and sustained for 4 h [27].…”
Section: Discussionmentioning
confidence: 99%